Microwave Selective Heating Assisted Distillation Process of Two Components System - Xing, J.Y.; Bai, B.; Song, X.L.; Yang, M.Y. (Asian Journal of Chemistry, 2014)
Microwave is widely used in heating process both at home and in the industry sector, due to its advantages, such as capacity to rapidly transmit heat, penetration power, convenience etc. The interest in microwave heating has been witnessed in the last 40 years by an increasing number of new applications and theoretical studies, but seldom investigation is focused on its selective heating based on dielectric constant of heated substance. In this paper, two-component miscible system is investigated in microwave field with or without vacuum, some parameters such as temperature rise, heat transfer, evaporation volume and other factors were analyzed. Microwave select heating process is preliminary understood and its potential application in molecular distillation is proved.